Recombinant Forms of Arginase and Arginine Deiminase as Catalytic Components of «Argitest» Enzymatic Kit for L-arginine Analysis - Stasiuk, N.Ye.; Gaida, G.Z.; Zakalskiy, A.Ye.; Zakalska, O.M.; Fayura, L.R.; Vovk, O.I.; Stasyk, O.V.; Sybirny, A.A.; Honchar, M.V. (Science and Innovation, 2024)
For the time, no screening test kits for L-arginine monitoring in biological fluids, including the blood, have been available in the arsenal of domestic clinical diagnostics. The Argitest enzymatic kit is based on the enzymatic-chemical method of L-arginine quantitative analysis developed using different forms of recombinant human liver arginase I (arginase) and arginine deiminase. The method is highly selective, cheap, simple, and fast. It is remarkable for stability of enzymes and final products. The article demonstrates the possibility of using recombinant arginine-selective enzymes in composition of Argitest kit. The catalytic and analytic characteristics of these enzymes have been studied. It has been showed that each enzyme can be used as a component of enzymatic kit.